Land restoration: a neglected task - Scharpenseel, H.W. (Technical Centre for Agricultural and Rural Cooperation, 1987)
H.W. ScharpenseelLand restoration: a neglected taskThere is much talk of the ecological disasters which result from clearing land by slash and burn: lowering of the water table, spreading savannah colonized by Imperata cylindrica, and...